REPRESSION OF LABOR RESOURCES BY THE PEOPLE'S COURTS IN THE UZBEK SSR (TAMADDUN NURI JURNALI, 2024)
In this article, during the Second World War, the militarization of enterprises and institutions, the restriction of the constitutional right of citizens to free choice of profession and labor, the brutal exploitation of the population, the use of tens of thousands of prisoners as free labor of the authoritarian Soviet regime are revealed using the example of the Uzbek SSR.